Association of NRAS Mutation With Clinical Outcomes of Anti-PD-1 Monotherapy in Advanced Melanoma: A Pooled Analysis of Four Asian Clinical Trials - Zhou, Li; Wang, Xuan; Chi, Zhihong; Sheng, Xinan; Kong, Yan; Mao, Lili; Lian, Bin; Tang, Bixia; Yan, Xieqiao; Bai, Xue; Li, Siming; Guo, Jun; et al. (Frontiers in Immunology, 2021)
Background: Anti-PD-1 monotherapy is the standard therapy for advanced melanoma patients, including those with NRAS mutations. The influence of NRAS mutation on immunotherapy, especially in noncutaneous melanoma, is largely uncharacterized. Materials and Methods: We analyzed clinical data of four clinical trials for advanced melanoma patients treated with anti-PD-1 monotherapy between 2016 and 2019. The impact of NRAS mutation on efficacy and outcome of immunotherapy were analyzed in cutaneous and noncutaneous groups separately. Results: A total of 206 patients were assessed, including 92 cutaneous melanoma patients with 12 NRAS mutations and 114 noncutaneous melanoma patients with 21 NRAS mutations. In cutaneous melanoma, the response rates of NRAS mutant patients were lower than patients without NRAS mutations (9.5% vs. 23.9%), the median progression-free survival (PFS) and median overall survival (OS) were shorter for patients with NRAS mutations, although without significant difference for OS (P=0.081). In noncutaneous melanoma, the response rates were 0 and 13.7% for NRAS mutant and wild-type patients, the median PFS were 3.6 months (95% CI: 0.9-6.3) and 4.3 months (95%CI: 2.9-5.7) (P=0.015), and the median OS were 10.8 months (95% CI: 1.5-20.1) and 15.3 months (95% CI: 13.2-17.4) (P=0.025), respectively. In multivariate analysis, NRAS mutation, along with ECOG performance score and LDH level, was negatively associated with both PFS (HR 1.912, P=0.044) and OS (HR 2.210, P=0.025) in noncutaneous melanoma. Conclusion: In advanced Asian melanoma treated with anti-PD-1 monotherapy, NRAS mutant patients had lower response rates and poorer prognoses compared to wild-type patients, especially in noncutaneous subtypes.